Pelatihan soft skills dan outbound bagi Guru-Guru dan Perangkat Desa Rantau Baru - Zulfan Saam; Raja Arlizon; Elni Yakub; Mahmud Alpusari; Dwi Novita Fani; Rusliyana Rusliyana (CANANG: Jurnal Pengabdian Masyarakat, 2021)
The population of Rantau Baru Village is 750 people. Most of the people's livelihood is fishing. There are eleven teachers in Rantau Baru Village, consisting of nine elementary school teachers and two kindergarten teachers. In addition, the number of village officials is eleven people. The purpose of this service activity is to provide an understanding to teachers and village officials about the importance of soft skills in improving teacher professionalism and service quality. In addition, outbound activities are also carried out which are useful as personality development. This service is carried out through: lecture and demonstration methods (Practice). The target group for this service is 22 people consisting of elementary school teachers, kindergarten teachers and village officials. The results of this service can increase the knowledge of participants about soft skills and personality. Another benefit for teachers and village officials is to strengthen personality aspects such as self-confidence, cooperation, courage, creativity, and social relations in improving the professionalism of teachers and village officials.